2005
DOI: 10.4049/jimmunol.175.12.7848
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of CD28 by Its Natural Ligand CD86 in the Absence of TCR Stimulation Induces Lipid Raft Polarization in Human CD4 T Cells

Abstract: Stimulation of resting CD4 T cells with anti-CD3/CD28-coated beads leads to rapid polarization of lipid rafts (LRs). It has been postulated that a major role of costimulation is to facilitate LR aggregation. CD86 is up-regulated or expressed aberrantly on immune cells in a wide array of autoimmune and infectious diseases. Using an Ig fusion with the extracellular domain of CD86 (CD86Ig) bound to a magnetic bead or K562 cells expressing CD86, we demonstrated that ligation of CD28 by its natural ligand, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…As such, many costimulatory ligands have limited activity as soluble proteins due to inefficient signal transduction (40,41,47). Although agonistic Abs against costimulatory receptors are effective in delivering immunological signals, there is evidence suggesting that signals delivered by Abs may quantitatively and qualitatively differ from signals transduced by natural ligands (37)(38)(39). In an attempt to use signaling via 4-1BB as an alternative to CD28-mediated costimulation for the expansion of Treg cells, we constructed a novel form of 4-1BBL chimeric with SA (SA-4-1BBL) that functions as a soluble protein.…”
Section: Generation Of a Chimeric 4-1bbl Molecule Having Potent Costimentioning
confidence: 99%
See 2 more Smart Citations
“…As such, many costimulatory ligands have limited activity as soluble proteins due to inefficient signal transduction (40,41,47). Although agonistic Abs against costimulatory receptors are effective in delivering immunological signals, there is evidence suggesting that signals delivered by Abs may quantitatively and qualitatively differ from signals transduced by natural ligands (37)(38)(39). In an attempt to use signaling via 4-1BB as an alternative to CD28-mediated costimulation for the expansion of Treg cells, we constructed a novel form of 4-1BBL chimeric with SA (SA-4-1BBL) that functions as a soluble protein.…”
Section: Generation Of a Chimeric 4-1bbl Molecule Having Potent Costimentioning
confidence: 99%
“…Under physiological conditions, costimulatory receptors are cross-linked by cell membrane-bound ligands (38,46). As such, many costimulatory ligands have limited activity as soluble proteins due to inefficient signal transduction (40,41,47).…”
Section: Generation Of a Chimeric 4-1bbl Molecule Having Potent Costimentioning
confidence: 99%
See 1 more Smart Citation
“…MIR1 downregulates all human class I MHC, gamma interferon receptor (IFN-␥R), and CD1d, whereas MIR2 downregulates a subset of MHC-I molecules (HLA-A and HLA-B), IFN-␥R, CD1d, platelet endothelial cell adhesion molecule 1 (PECAM-l), intercellular adhesion molecule 1 (ICAM-l), B7.2, bone marrow stromal cell antigen 2 (BST-2), syntaxin 4, and activated leukocyte cell adhesion molecule (ALCAM; CD166) (2,5,6,15,16,21,23,24,30). Most of these substrates are known to reside in, or upon activation are recruited to, lipid rafts (8,18,32,35), microdomains of the plasma membrane thought to be important for a wide range of signal transduction events, including T cell and B cell activation.Posttranslational modifications can target proteins to specific regions of the plasma membrane. Palmitoylation is a type of fatty acid modification in which palmitic acid is attached to sulfur atoms of cysteine residues, making polypeptides more hydrophobic.…”
mentioning
confidence: 99%
“…Our rationale was that sustained heating seems to be able to replace at least some of the function of costimulation through CD28, which is known to be mediated through cholesterol-dependant nanodomain reorganization at the cell surface. 35 In addition, Brameshuber et al demonstrated that fever-range heat induced raft-destabilization/reorganization in living cells. 36 Could the co-stimulatory cues (e.g.…”
Section: Cd4c T Cells From (A) Wild Type and (B) Cd28mentioning
confidence: 99%